I-DO GOC: Improving documentation in oncology with goals of care. Issue 28 (1st October 2022) - Martinez, Francisco; Hauser, Karen; Aller, Ashley; Shirazi, Aida; Lin, Amy Ying Ju; Lim, Peggy T; Jones, Tyler; Whitehead, Hannah; Risbud, Amita; Yen, Sue May; Liu, Raymond; Katzel, Jed Abraham
Abstract : 314 Background: Goals of Care (GOC) discussions are part of high-quality care, allowing clinicians to align the care provided with what is most important to the patient. Early GOC discussions are associated with better quality of life, reduced use of futile medical care, and enhanced goal-concordant care. In order to increase GOC documentation within the electronic medical record (EMR), the Kaiser Permanente San Francisco medical oncology practice began an ASCO Quality Training Program initiative in January 2022 to increase oncologist discussion and documentation of GOC in advanced cancer patients. Methods: Baseline data on the frequency of GOC discussions was obtained through a structured chart review with a historical cohort of stage IV or recurrent cancer patients > 18 years old between 1/1/2020-6/1/2020. The project aimed to improve accessible GOC documentation from a baseline of 0% to a goal of 25% among stage IV or recurrent cancer patients seen by an oncologist between 1/2022 and 5/14/2022. Patients with hematologic malignancies were excluded. Oncologists were instructed to use a templated GOC automated phrase (Smartphrase) that consolidated content into a visible, centralized EMR location. The frequency of GOC Smartphrase usage among oncologists was tracked monthly through a customized dashboard. Plan-Do-Study-Act cycles included education on GOC documentation and monthly feedback for oncologists on performance. Results: Review of the 2020 historical cohort revealed no structured or accessible GOC documentation by oncologists. During the intervention period, 300 Stage IV and recurrent cancer patients were eligible for GOC documentation. The median age of the intervention group was 70 years, with the most common types of cancers represented: Prostate (21%), Breast (19%), and Lung (17%). Our study cohort included a diverse population: White (45%), Asian (36%), Black/African American (11%), and Hispanic (7%). Between 1/1/2022 to 5/14/22, 142 (47%) patients had at least one documented GOC conversation, exceeding the target of 25%. 100% of these structured conversations were viewable in the designated area in the EMR. Conclusions: Our ASCO Quality Training Program initiative successfully increased oncologists' overall number of GOC conversations and made those conversations more easily accessible to the entire care team. Our process for standardizing the documentation of GOC conversations was based on the use of a Smartphrase that helped organize the collected information within the EMR. During the study period, we increased the documented GOC rate from 0% to 47%. This can improve patient and physician satisfaction, as well as improve goal concordant care for patients with advanced cancer. Further efforts will be focused on sustaining these initial gains in GOC documentation and on promoting their broader use across our organization.